البنيان القانوني للسفتجة الإلكترونية على ضوء قانون التوقيع الإلكتروني والمعاملات الإلكترونية العراقي: دراسة قانونية - فيض الله، حسين توفيق Faidullah, Hussein Tawfiq; مصطفى، سميرة عبدالله (جامعة بغداد - كلية القانون, 2015)
البحث يسلط الضوء على معالجة المشرع العراقي للأوراق التجارية الإلكترونية في قانون التوقيع الإلكتروني والمعاملات الإلكترونية رقم (78) لسنة (2013) ويبحث في بيان طبيعة السفتجة الإلكترونية ومدى إمكانية حلولها محل السفتجة الورقية، واستمرارها كأداة وفاء وائتمان في التعاملات التجارية وخاصة في تسوية الديون الخارجية ومنافسة وسائل الدفع والائتمان الإلكترونية الأخرى، وبيان ما إذا كان بالإمكان إيجاد البديل الإلكتروني للتظهير والقبول اللذان يميزان التعامل بالسفتجة التقليدية، وإلى أي مدى كان المشرع العراقي موفقا في معالجته للموضوع وتوصلنا إلى مقترحات عدة لضمان المعالجة القانونية الناجعة لهذه الأوراق.
This paper sheds some light on the solutions provided for by the Iraqi legislator regarding securities under the provisions of the Law, No. 78 of 2013 (Law of electronic signature and electronic transactions). Secondly, it explores the legal nature of electronic promissory note and to what extent it can be used instead of the classical promissory note as its continuity as a means of the fulfillment of debts and credits specifically for paying external debts, and as a means of competing with other instrument of electronic pay back of debts. Thirdly, it also clarifies whether this electronic promissory note can be an alternative for electronic signature and acceptance of a promissory note. Further, it explains whether the Iraqi legislator has successfully tackled the issue? Finally, it comes up with certain suggestions in this regard in order to insure finding a successful legal solution for the issue in question.
Keywords: الأوراق التجارية -- السفتجة الإلكترونية -- التوقيع الإلكتروني -- القانون التجاري -- العراق